Research Progress: Instituto de Investigaciones en Ciencias Biomédicas (INICIB), Universidad Ricardo Palma: Avances en investigación: Instituto de Investigaciones en Ciencias Biomédicas (INICIB), Universidad Ricardo Palma - De La Cruz-Vargas, Jhony A. (2021)
One of the essential functions of the university is to promote, support and strengthen research, as a source to generate new knowledge and as a scientific tool in search of practical solutions to everyday problems in society. The Universidad Ricardo Palma, represented by their dean as its highest authority, offers the university’s academic framework and the institution’s policies will in order to move forward in research policies.